Fungal-Bacterial Cooccurrence Patterns Differ between Arbuscular Mycorrhizal Fungi and Nonmycorrhizal Fungi across Soil Niches - Mengting Maggie Yuan (American Society for Microbiology, 2021)
Soils near living and decomposing roots form distinct niches that promote microorganisms with distinctive environmental preferences and interactions. Yet few studies have assessed the community-level cooccurrence of bacteria and fungi in these soil niches as plant roots grow and senesce.